-7(-7r-7)+4(1-r)=-37

Simple and best practice solution for -7(-7r-7)+4(1-r)=-37 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(-7r-7)+4(1-r)=-37 equation:


Simplifying
-7(-7r + -7) + 4(1 + -1r) = -37

Reorder the terms:
-7(-7 + -7r) + 4(1 + -1r) = -37
(-7 * -7 + -7r * -7) + 4(1 + -1r) = -37
(49 + 49r) + 4(1 + -1r) = -37
49 + 49r + (1 * 4 + -1r * 4) = -37
49 + 49r + (4 + -4r) = -37

Reorder the terms:
49 + 4 + 49r + -4r = -37

Combine like terms: 49 + 4 = 53
53 + 49r + -4r = -37

Combine like terms: 49r + -4r = 45r
53 + 45r = -37

Solving
53 + 45r = -37

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '-53' to each side of the equation.
53 + -53 + 45r = -37 + -53

Combine like terms: 53 + -53 = 0
0 + 45r = -37 + -53
45r = -37 + -53

Combine like terms: -37 + -53 = -90
45r = -90

Divide each side by '45'.
r = -2

Simplifying
r = -2

See similar equations:

| 8x+2+4x+18=0 | | -(-w-4)=-w-4 | | 3x-15=1+5x-30 | | 7y+96=180 | | 21+4x=8y | | 6x+4+4x+8=52 | | 95=5v+10 | | 7y+22=180 | | x+(x+1)=5-3x | | 55=-7v | | -62=-5x+3(1+6x) | | x=11/cos(24) | | x=11*cos(24) | | 3(2z-4)+9=15 | | X^2+y^2+32x-24y+391=0 | | 2834=26(p+30) | | 10=4(x-5) | | -log(x)=3.74 | | A=b+47 | | -16=-4(3n+1) | | y=3x+14z | | 0=-X+2COSX | | 3x+14z=y | | -72=-8(-6x-3) | | x^3+x^2*6+x^2*2+x*12=240 | | 0.428571428571x-14=0.714285714286x+2 | | 24=-8(-9+1) | | 3*a=7.5 | | 2x-7=c | | 0=X^3+4x^2-5x | | (7b-2)(7b+2)= | | 6(x+1)+2=14 |

Equations solver categories